Neglected Monteggia fracture dislocations in children. Issue 3 (May 2015) - Goyal, Tarun; Arora, Shobha S.; Banerjee, Sumit; Kandwal, Pankaj
<x xml:space="preserve">Abstract</x> Monteggia fractures are uncommon and frequently missed injuries in children. This article aims to study, in a systematic manner, the surgical management and complications of treatment of chronic radial head dislocations. After screening of relevant abstracts, a total of 28 studies were included in the systematic review. A narrative synthesis of various treatment modalities has been discussed. This article concludes that open reduction should be attempted unless dysmorphism of the radial head restricts it. Open reduction with ulnar osteotomy with or without annular ligament reconstruction is the most commonly performed procedure and is expected to result in reduced pain and elbow deformity.